Upaya Guru BK Dalam Menghadapi Sifat Negatif Pada Siswa di SMPN 35 Medan - Annisa Maharani Nasution Maharani Nasution; Rhiza Khairani; Tasya Amalia; Dika Sahputra (Peneliti.net, 2022)
Students in Junior High School (SMP) or equivalent are in a phase from adolescence to adulthood, because they are unstable because they are eas ilyinfluenced by the outside world. So they are contaminated and a ffect their lifestyle, as well as their morals, which causes them to be comenaughty. Not infrequently wealsoen counter thesethings in schools. Therefore, counseling teachers have an importantrole in over coming delinquency in schools. This type of researchis descriptive qualitative. The method that the researcher usesis by collecting data through counseling teachers, reducing data and drawing conclusions. The results of the research on the effort sof this counseling teacher in over coming the negative nature of students at SMPN 35 Medan.